2001
DOI: 10.1046/j.1525-1470.2001.1862004.x
|View full text |Cite
|
Sign up to set email alerts
|

New‐Onset Ichthyosis and Diabetes in a 14‐Year‐Old

Abstract: Diabetes has not been linked to acquired ichthyosis or ichthyosis vulgaris. We report a newly diagnosed diabetic 14-year-old girl with bilateral tibial and sacral ichthyosiform plaques and a hemoglobin A1c of 20.1%. The patient had no personal or family history of atopy or ichthyosis and lacked keratosis pilaris or hyperlinear palms. A biopsy specimen of an ichthyosiform plaque showed compact lamellar orthohyperkeratosis and hypogranulosis, histopathology consistent with either ichthyosis vulgaris or acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…As a group, CAII comprising lipohypertrophy, PIH, lipoatrophy, acanthosis nigricans, and other infrequent lesions such as urticarial reactions, folliculitis and keloid were the most common findings, contrary to previous studies, in which ichthyosiform skin changes was the most frequent finding. It could be due to reporting of asteototic eczema as acquired ichthyosis . Raile et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a group, CAII comprising lipohypertrophy, PIH, lipoatrophy, acanthosis nigricans, and other infrequent lesions such as urticarial reactions, folliculitis and keloid were the most common findings, contrary to previous studies, in which ichthyosiform skin changes was the most frequent finding. It could be due to reporting of asteototic eczema as acquired ichthyosis . Raile et al .…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to reporting of asteototic eczema as acquired ichthyosis. 7 Raile et al 8 reported lipohypertrophy in 43Á7% of 112 patients with type 1 DM. Hajheydari et al 9 documented a higher frequency of lipohypertrophy in patients with type 1 DM compared with type 2 DM (37Á5% vs. 6Á7%).…”
Section: Discussionmentioning
confidence: 99%
“…Имеются две публикации, в которых описывается сочетание СД 1-го типа и приобретенного ихтиоза, а также сочетание ихтио-зиформного дерматоза с СД 2-го типа [16,17]. В первой публикации приведено описание 14-летней девушки афроамериканского происхождения, стра-дающей СД 1-го типа в течение 6 мес.…”
Section: проблемы эндокринологии 4 2013unclassified
“…Diabetes has not been definitively linked to acquired ichthyosis or ichthyosis vulgaris; however, there are case reports associating new onset ichthyosis with diabetes. 6 Fetal skin biopsy at approximately 19 weeks may provide an early diagnosis of certain forms of ichthyosis (i.e. Harlequin type, which is extremely severe and usually fatal.…”
Section: Diagnosismentioning
confidence: 99%